ANALISIS PROFIL KOMPETENSI KEAHLIAN AGRIBISNIS TANAMAN PANGAN DAN HORTIKULTURA BERBASIS INDUSTRI DISEKOLAH MENENGAH KEJURUAN - Indah Herawati; Husain Syam; Andi Sukainah (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This research aims to; know the profile of Competence of Food Crops and Horticulture Agribusiness Expertise;know relevance Competence of Food Crops and Horticulture Agribusiness Skills with DU/DI. This research method is a survey that uses a quantitative approach with descriptive analysis techniques. The research subjects are industries engaged in Food Crops and Horticulture Agribusiness and Vocational High Schools which have competency programs for Food Crops and Horticulture Agribusiness expertise in South Sulawesi Province. Research result Analysis of Competency Profiles of Industry-Based Agribusiness Food Crops and Horticulture Expertise in Vocational High Schools;The Competency Aspect of the Basics of Plant Cultivation is the only aspect of competence of which the thirteen basic competencies are applied by all schools that are sampled. . Competency Aspects of Nursery and Plant Tissue Culture are aspects that have at least the most maximally applied basic competencies. Aspects of Creative Product Competence and Entrepreneurship are the last aspects of the Agribusiness and Horticulture Agribusiness Skills Competence;Relevance Competence expertise of Food Crops and Horticulture Agribusiness with DU/DI is very Relevant, for PT. East West Seed Indonesia is the industry that has the highest relevance value, which is 24% and for the Bunga Cap Tanah Merah farmer group, it is the industry that has the lowest relevance value, which is 13%.